The Childfree Phenomenon and Its Impact on Family Resilience: An Islamic Legal Perspective - Abdul Latief, Muhammad; Sri Insani, Silvi; Ardianto, Firdaus; Hafizi, Ihsanul; Nurhaliza, Pioni (Samara: Journal of Islamic Law and Family Studies, 2024)
The childfree phenomenon is becoming an increasingly discussed topic in the modern era, including in Indonesia. In a society that culturally and religiously considers children to be a blessing and the main purpose of marriage, the childfree choice raises controversy and debate, especially when examined from the perspective of Islamic family law. This study aims to analyze how the childfree phenomenon is viewed from the perspective of Islamic law and to what extent this decision impacts family resilience. The study is motivated by the increasing number of couples choosing not to have children for reasons such as career, personal freedom, or concerns about social and environmental conditions. The research method used is a qualitative approach with literature review and normative analysis of verses from the Quran, hadith, and opinions of scholars regarding the command to have children and the purpose of marriage in Islam. Additionally, the researcher also uses a sociological approach by referring to theories of family resilience to assess the practical impact of childfree within the structure of Muslim families. Data was obtained from scientific literature, Islamic documents, and in-depth interviews with several Muslim couples who practice the childfree principle. The main findings of this study indicate that although Islam does not explicitly prohibit childfree, there is a strong encouragement in Islamic teachings to have children as a form of continuing the family line, strengthening family bonds, and fulfilling the maqashid al-syari'ah.